Phosphine-ligated dinitrosyl iron complexes for redox-controlled NO release. Issue 25 (31st May 2016) - Wittkamp, F.; Nagel, C.; Lauterjung, P.; Mallick, B.; Schatzschneider, U.; Apfel, U.-P.
Abstract : Herein we report on the redox-controlled NO release from four dinitrosyl iron compounds (DNICs). Abstract : Here we present the syntheses and structural, spectroscopic, as well as electrochemical properties of four dinitrosyl iron complexes (DNICs) based on silicon- and carbon-derived di- and tripodal phosphines. Whereas CH3 C(CH2 PPh2 )3 and Ph2 Si(CH2 PPh2 )2 coordinate iron in a η 2 – binding mode, CH3 Si(CH2 PPh2 )3 undergoes cleavage of one Si–C bond to afford [Fe(NO)2 (P(CH3 )Ph2 )2 ] at elevated temperatures. The complexes were characterized by IR spectroelectrochemistry as well as UV-vis measurements. The oxidized {Fe(NO)2 } 9 compounds were obtained by oxidation with (NH4 )2 [Ce(NO3 )6 ] and their properties evaluated with Mössbauer and IR spectroscopy. Stability experiments on the complexes suggest that they are capable of releasing their NO-ligands in the oxidized {Fe(NO)2 } 9 but not in the reduced {Fe(NO)2 } 10 form. A detailed DFT analysis is provided in order to understand the electronic configurations and the complexes' ability to release NO.